16 - r(t(R)) =t(R) I X t(r(R)) = t(R I X ) = (R I X ) (R I...

Info iconThis preview shows pages 1–2. Sign up to view the full content.

View Full Document Right Arrow Icon
166 X 6 ,R 6 X ) (2) r±(t±(R)±)±=±t(r(R)) 6 26 6 a6 R16 R2 R36 =±6 R1±R26 R1± R36 6 R2 R36 R1=±6 R2±±R16 R3±±R16 6 b6 (R ±I X ) ±n =±I X ± ±R R ±2 ±R ±3 ∪…∪ R ±n 6 n 6 n=16 (R ±I X ) ±1 =±I X ± ±R6 6 n=k ± 6 6 (R ±I X ) ±k =±I X ± ±R 2 ±R ±3 ∪…∪ R ±k ± 6 n=k+1,±(R ±I X ) ±k±+1 =(R ±I X ) ±k ±(R ±I X ) =±(I X ± ±R R ±2 ±R ±3 ∪…∪ R ±k )±(R ±I X ) =( ± R R 2 ± 3 ∪…∪ R k ± ± R ± k ± +1 ) ± (I X ± ± R R 2 ± R± 3 ∪…∪ R ±k ) =±I X ± ±R R ±2 ±R ±3 ∪…∪ R ±k ± ±R ±k±+1
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
Background image of page 2
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: r(t(R)) =t(R) I X t(r(R)) = t(R I X ) = (R I X ) (R I X ) 2 (R I X ) 3 (R I X ) n =(R I X ) ( I X R R 2 ) ( I X R R 2 R 3 ) (I X R R 2 R 3 R n ) = I X R R 2 R 3 R n = I X t (R) = t (R) I X 6 3 r (t (R) ) = t(r(R))...
View Full Document

This note was uploaded on 02/06/2011 for the course CS 343 taught by Professor Zhoujunli during the Spring '08 term at BUPT.

Page1 / 2

16 - r(t(R)) =t(R) I X t(r(R)) = t(R I X ) = (R I X ) (R I...

This preview shows document pages 1 - 2. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online